Thrombocytopenia in pregnancy - Tiwari, Nikita; Anjali Kanhere; Satarupa Paul Dutta; Nipun Madhav (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Thrombocytopenia is defined as a platelet count of <150x109/l. It is the second most common hematological abnormality during pregnancy. We present a case series of thrombocytopenia in pregnancy. The aim of this study was to evaluate thrombocytopenia in pregnancy at tertiary care center, Bhopal and to identify, treat and assess the maternal complications and neonatal outcome. In a year, 10 cases were evaluated out of which the diagnosis of 3 cases was immune thrombocytopenic purpura, 3 cases of gestational thrombocytopenia, 3 cases of thrombocytopenia associated with hypertensive disorders of pregnancy and 1 case of HBV induced chronic liver disease associated with thrombocytopenia.